High-adhesion friction-resistant anticorrosive paint as well as preparation method and application thereof
By using alternating copolymerization and graft copolymerization reactions of materials such as epoxy resin, composite resin, graft monomer, etc. in the anticorrosion coatings of power equipment, a stable polymer network structure is formed, which solves the adhesion and friction resistance of existing anticorrosion coatings. The problem of insufficient performance and hardness significantly improves the wear resistance and corrosion resistance of the coating.
Patent Information
- Application Number
- CN202411653445.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
Due to poor adhesion, friction resistance and hardness in power equipment, existing anticorrosion coatings are prone to cracking and falling off after long-term use, and cannot effectively prevent corrosion and wear of metal substrates.
Using a high adhesion friction-resistant anti-corrosion coating, the formulation includes epoxy resin, composite resin, graft monomer, anti-corrosion reinforcement filler and friction-resistant filler. Through alternating copolymerization and graft copolymerization reactions, a stable polymer network is formed. Structure, improves the impact resistance, lubricity and adhesion of the coating.
It significantly improves the high temperature resistance, adhesion and wear resistance of the coating, extends the service life of the metal, and enhances the corrosion and wear resistance of power equipment.
Smart Images

Figure CN119463616A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-corrosion coatings for electric power equipment, and in particular to a high-adhesion, friction-resistant and anti-corrosion coating and a preparation method and application thereof. Background Art
[0002] The corrosion and failure of metals are widespread in all areas of the national economy, and are related to the safety of people's lives and property, industrial and agricultural production, and power transmission. With the rapid development of the national economy and the commissioning of a large number of power projects, many power equipment such as disconnector transmission mechanisms and power fittings will wear and damage the surface of the anti-corrosion coating during operation and operation. The metal substrate that loses the protection of the anti-corrosion coating will accelerate corrosion, which will lead to failure of the power equipment. At present, the research on anti-corrosion coatings commonly used in power equipment mainly focuses on improving the anti-corrosion performance of coatings by adding hyperbranched polymers, polyurethanes, polysilazane resins, etc., by physically blending or chemically modifying epoxy resins. However, due to its general adhesion, friction resistance and hardness, its application under the above harsh conditions is limited. Under long-term wear, the coating is prone to cracking and falling off, which cannot meet the daily use of the above-mentioned power equipment.
[0003] Therefore, it is necessary to develop an anti-corrosion coating with excellent anti-corrosion effect, high adhesion and friction resistance, which can form an anti-corrosion, wear-resistant and highly adhesive coating after being applied to the metal substrate. This is of great significance for reducing the corrosion and wear of power equipment and improving the service life of power equipment. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the existing anti-corrosion coatings have poor anti-corrosion performance, adhesion performance, wear resistance and hardness. The purpose is to provide a high-adhesion and friction-resistant anti-corrosion coating and its preparation method and application, which solves the problems of poor anti-corrosion effect, poor adhesion, low friction resistance and poor hardness of the existing anti-corrosion coatings.
[0005] The present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a high-adhesion, friction-resistant and anti-corrosion coating, comprising the following raw materials in parts by weight:
[0007] 20-80 parts of epoxy resin, 5-40 parts of composite resin, 5-40 parts of grafting monomer, 0.5-10 parts of anti-corrosion reinforcing filler, 1-20 parts of friction-resistant filler, 5-40 parts of curing agent and 50-150 parts of acetone.
[0008] As a possible design, the epoxy resin is a 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin.
[0009] As a possible design, the composite resin is polyethylene glycol bismaleimide resin.
[0010] As a possible design, the grafting monomer is dopamine methacrylamide.
[0011] In a second aspect, the present invention provides a method for preparing a high-adhesion friction-resistant anti-corrosion coating, comprising the following steps:
[0012] The curing agent is heated, and the composite resin is added under stirring conditions, and after stirring and reacting, the epoxy resin and the grafting monomer are added, and after stirring and reacting, a mixed system is obtained;
[0013] The mixed system is cooled, acetone, anti-corrosion reinforcing filler and friction-resistant filler are added, and after stirring, a high-adhesion friction-resistant anti-corrosion coating is obtained.
[0014] As a possible design, the curing agent is heated to 70-120°C.
[0015] As a possible design, after the curing agent is heated, the composite resin is added at a rotation speed of 800 to 1200 rpm, and the stirring reaction is maintained for 5 to 40 minutes, and then the epoxy resin and the grafting monomer are added, and the stirring reaction is continued for 50 to 30 minutes to obtain a mixed system.
[0016] As a possible design, the mixed system is cooled to 15-35°C, acetone, anti-corrosion reinforcing filler and friction-resistant filler are added, and stirred for 5-60 minutes to obtain a highly adhesive friction-resistant anti-corrosion coating.
[0017] As a possible design, after adding acetone, anti-corrosion reinforcing filler and friction-resistant filler, ultrasonic stirring is performed for 5 to 60 minutes.
[0018] In a third aspect, the present invention provides an application of a high-adhesion, friction-resistant and anti-corrosion coating, comprising: coating the coating on a substrate to form a coating, wherein the substrate is a metal or an alloy.
[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0020] The present invention can improve the comprehensive properties of the material, such as strength, modulus, heat resistance, etc., by alternately copolymerizing epoxy resin and composite resin to generate addition reaction to form a stable polymer; then graft copolymerization is performed with a grafted monomer to increase the crosslinking density of the material and form an interpenetrating network structure, thereby improving the impact resistance, lubricity, water resistance and adhesion to the substrate of the entire epoxy coating, and can also significantly improve the high temperature resistance, adhesion and wear resistance of the coating; then adding anti-corrosion reinforcing fillers can improve the mechanical properties and anti-corrosion properties of the coating; the added friction-resistant filler can not only isolate water vapor from entering the interior of the anti-corrosion coating, improve the resistance of the entire coating to wet and hot environments, but also serve as a protective layer to reduce the wear and damage of the coating caused by frequent friction, and improve the hardness and wear resistance of the coating surface.
[0021] The coating prepared by the present invention has been tested and found that when the coating thickness reaches 300 μm, the Shore hardness of the anti-corrosion coating is 96D, the adhesion is 21.5 MPa, and the specific wear rate is 0.8×10 -6 mm 3 / Nm, and the neutral salt spray resistance exceeds 1500 hours. Compared with the coating prepared with bisphenol A epoxy resin, the hardness, adhesion and neutral salt spray resistance time are increased by 20%, 112% and 90% respectively; the specific wear rate is reduced by 43%. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0023] Figure 1 The synthetic route and structural formula diagram of the epoxy resin of the present invention are shown in FIG. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0025] Since existing anti-corrosion coatings cannot combine the performance characteristics of good adhesion to metal surfaces, good friction resistance, good hardness and good corrosion resistance, the coatings formed by existing coatings crack and fall off after long-term use, causing oxidation, corrosion and wear on the metal surface, thereby shortening the life of the metal and easily causing failures of power equipment.
[0026] Based on the above reasons, the present invention provides a high-adhesion, friction-resistant and anti-corrosion coating, which, after forming a coating on the surface of a metal or alloy, has the performance advantages of good adhesion to the metal surface, good friction resistance, good hardness and good corrosion resistance, thereby extending the service life of the metal and ensuring the normal operation of power equipment.
[0027] In a first aspect, the present invention provides a high-adhesion, friction-resistant and anti-corrosion coating, comprising the following raw materials in parts by weight:
[0028] 20-80 parts of epoxy resin, 5-40 parts of composite resin, 5-40 parts of grafting monomer, 0.5-10 parts of anti-corrosion reinforcing filler, 1-20 parts of friction-resistant filler, 5-40 parts of curing agent and 50-150 parts of acetone.
[0029] On the one hand, epoxy resin has a high epoxy value and provides a large number of reaction sites, which can promote the cross-linking reaction of monomers, improve the cross-linking density and molecular weight of the resin, and ensure its excellent friction resistance and thermal stability; on the other hand, epoxy resin introduces biphenyl structure in the main chain. Biphenyl is a structural unit with high rigidity. On the one hand, it can improve the structural stability and friction resistance of the material, and on the other hand, it can reduce the free volume, thereby improving the toughness of the material and reducing water absorption. It is copolymerized with the composite resin. Since the composite resin structure contains carbon-carbon double bonds, it is easy to undergo addition reaction with substances containing active hydrogen. Epoxy resin is a thermosetting epoxide polymer. Its molecules contain active epoxy groups and can undergo cross-linking reaction with various types of curing agents. Therefore, epoxy resin and composite resin can undergo addition reaction under specific conditions to form a stable polymer. This polymerization reaction is expected to improve the comprehensive properties of the material, such as strength, modulus, heat resistance, etc. The grafted monomer reacts with it to form an interpenetrating network structure, which improves the impact resistance, lubricity, water resistance and adhesion to the substrate of the entire epoxy coating. Adding anti-corrosion reinforcing fillers and friction-resistant fillers can improve its anti-corrosion and wear-resistant properties.
[0030] In some embodiments of the present invention, the epoxy resin is a 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin.
[0031] 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether epoxy resin is synthesized from vanillin, which is derived from renewable plant resources. It effectively reduces dependence on fossil raw materials and significantly reduces carbon footprint, which is in line with the green chemistry and sustainable development needs under the dual carbon goals. Among them, each 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether epoxy resin monomer molecule contains 6 epoxy groups. The high epoxy value provides a large number of reaction sites, which can promote the cross-linking reaction of the monomer, which is beneficial to improve the cross-linking density and molecular weight of the resin, and ensure its excellent friction resistance and thermal stability. At the same time, the biphenyl structure is introduced into the main chain. Biphenyl is a structural unit with high rigidity. On the one hand, it can improve the structural stability and friction resistance of the material, and on the other hand, it can reduce the free volume, thereby improving the toughness of the material and reducing water absorption. In addition, the large number of hydroxyl and ether oxygen groups in the bio-based components effectively enhance the adhesion between the molecules and the substrate surface, allowing the coating to firmly adhere to the metal surface and not easily fall off. In summary, the 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether epoxy resin prepared from the extract of renewable vanilla beans has the characteristics of strong adhesion, good friction resistance, high chemical corrosion resistance and excellent electrical insulation.
[0032] Preferably, refer to Figure 1 The above-mentioned 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin is synthesized using vanillin, a main component of the natural extract of vanilla beans, as a monomer.
[0033] In some embodiments of the present invention, the composite resin is polyethylene glycol bismaleimide resin.
[0034] Polyethylene glycol bismaleimide resin is alternately copolymerized with the above-mentioned 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin. Polyethylene glycol bismaleimide resin contains carbon-carbon double bonds in its molecular structure, which is easy to undergo addition reaction with substances containing active hydrogen. 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin is a thermosetting epoxide polymer, which contains active epoxy groups in its molecules and can undergo cross-linking reaction with various types of curing agents. Therefore, under certain circumstances, the carbon-carbon double bonds of polyethylene glycol bismaleimide resin may undergo addition reaction with the epoxy groups of 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin to form a more stable polymer. Containing benzene rings, imide heterocycles and high cross-linking density makes the cured product have excellent heat resistance. This polymerization reaction is expected to improve the comprehensive properties of the material, such as strength, modulus, heat resistance, etc. At the same time, primary amines and secondary amines are conducive to the adhesion of the coating, thereby improving the hardness, friction resistance and adhesion of the coating on the substrate. In addition, the introduction of polyethylene glycol flexible molecular chains overcomes the shortcomings of high brittleness, poor impact strength, low elongation at break, and low fracture toughness of the cured product due to excessive cross-linking density and excessive rigidity of the molecular chain, further improving the adhesion, friction resistance and corrosion resistance of the material.
[0035] In some embodiments of the present invention, the grafting monomer is dopamine methacrylamide.
[0036] Dopamine methacrylamide is grafted and copolymerized on 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether epoxy resin. The molecular structure of dopamine methacrylamide includes double bonds. The opening polymerization of double bonds increases the crosslinking density of the material and forms an interpenetrating network structure, thereby improving the impact resistance, lubricity, water resistance and adhesion to the substrate of the entire epoxy coating. The amide group can interact with 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether epoxy resin and polyethylene glycol bismaleimide resin through hydrogen bonds. At the same time, the strong polarity of the amide group can form an induced dipole with the metal surface, and with its own permanent dipole, a strong adsorption is formed, thereby significantly improving the high temperature resistance, adhesion and anti-wear properties of the grease. The catechol group can mimic the structure of mussel adhesion protein polymers to improve the adhesion of materials: catechol coordinates with metal ions to form metal catechol complexes, forming a balance of oxidation and coordination, which can react with the metal matrix, transforming the adhesion between traditional epoxy resin coatings and metal substrates from physical action to chemical bonding, making 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin coatings have better adhesion on metal substrates and are less likely to fall off.
[0037] Preferably, the above-mentioned anti-corrosion reinforcing filler includes one or more of zinc powder, magnesium powder and aluminum powder.
[0038] More preferably, the above-mentioned anti-corrosion reinforcing filler is a mixed system of zinc powder, magnesium powder and aluminum powder, and the weight ratio of zinc powder, magnesium powder and aluminum powder is 1:1:1.
[0039] Zinc powder, magnesium powder and aluminum powder first act as reinforcing fillers to improve the mechanical properties of epoxy coatings. At the same time, zinc powder and magnesium powder act as anodes in electrochemical corrosion with steel, playing a role of cathodic protection, which can effectively slow down the corrosion of steel and work synergistically with polymer coatings to enhance the anti-corrosion performance of epoxy coatings.
[0040] Preferably, the above-mentioned friction-resistant filler includes one or more of flaky aluminum oxide, flaky aluminum nitride and flaky silicon carbide.
[0041] Choosing flaky aluminum oxide, flaky aluminum nitride and flaky silicon carbide as friction-resistant fillers can not only prevent moisture from entering the interior of the anti-corrosion coating and improve the stability of the entire coating in a humid and hot environment, but also serve as a protective layer to reduce the wear and damage to the coating caused by frequent friction and improve the hardness and wear resistance of the coating surface.
[0042] Preferably, the curing agent is selected from one or more of 4,4'-diaminophenylsulfone, dimethylimidazole and diethylenetriamine.
[0043] Preferably, the above-mentioned high-adhesion friction-resistant anti-corrosion coating comprises the following raw materials in parts by weight:
[0044] 30-60 parts of epoxy resin, 10-30 parts of composite resin, 10-30 parts of grafting monomer, 2-7 parts of anti-corrosion reinforcing filler, 5-15 parts of friction-resistant filler, 10-30 parts of curing agent and 80-120 parts of acetone.
[0045] More preferably, the above-mentioned high-adhesion friction-resistant anti-corrosion coating comprises the following raw materials in parts by weight:
[0046] 45 parts of epoxy resin, 20 parts of composite resin, 15 parts of grafting monomer, 5 parts of anti-corrosion reinforcing filler, 10 parts of friction-resistant filler, 20 parts of curing agent and 100 parts of acetone.
[0047] In a second aspect, the present invention provides a method for preparing a high-adhesion friction-resistant anti-corrosion coating, characterized in that it comprises the following steps:
[0048] S1. Heat the curing agent, add the composite resin under stirring conditions, stir and react, add the epoxy resin and the grafting monomer, stir and react, and obtain a mixed system.
[0049] In some embodiments of the present invention, the curing agent is heated to 70-120°C.
[0050] In some embodiments of the present invention, after the curing agent is heated, the composite resin is added at a rotation speed of 800 to 1200 rpm, and the stirring reaction is maintained for 5 to 40 minutes, and then the epoxy resin and the grafting monomer are added, and the stirring reaction is continued for 50 to 30 minutes to obtain a mixed system.
[0051] S2. Cooling the mixed system, adding acetone, anti-corrosion reinforcing filler and friction-resistant filler, and stirring to obtain a high-adhesion friction-resistant anti-corrosion coating.
[0052] In some embodiments of the present invention, the mixed system is cooled to 15-35° C., acetone, anti-corrosion reinforcing filler and friction-resistant filler are added, and stirred for 5-60 minutes to obtain a highly adhesive friction-resistant anti-corrosion coating.
[0053] In some embodiments of the present invention, after adding acetone, anti-corrosion reinforcing filler and friction-resistant filler, ultrasonic stirring is performed for 5 to 60 minutes.
[0054] In a third aspect, the present invention provides an application of a high-adhesion, friction-resistant and anti-corrosion coating, comprising: coating the coating on a substrate and curing it at room temperature to form a coating, wherein the substrate is a metal or an alloy.
[0055] Preferably, before coating the substrate, the surface of the substrate is cleaned and dried.
[0056] Example 1
[0057] A high-adhesion friction-resistant anti-corrosion coating is prepared by the following method:
[0058] 100 g of 4,4'-diaminophenylsulfone was placed in a reactor and heated to 120°C. Then, 200 g of polyethylene glycol bismaleimide resin was added to the reactor at a speed of 1000 rpm, and the mixture was stirred for reaction for 10 minutes. Then, 600 g of 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin and 150 g of dopamine methacrylamide were added, and the mixture was stirred for reaction for 10 minutes to obtain a uniform mixed system.
[0059] The reactor was removed from the heat source, stirring was maintained, the temperature was lowered to room temperature, and then 500 g of acetone, 20 g of zinc powder, an anti-corrosion reinforcing filler, and 50 g of flaky aluminum oxide, an anti-friction filler, were added, and ultrasonic stirring was performed for 50 minutes to obtain a highly adhesive anti-friction and anti-corrosion coating.
[0060] The surface of the metal substrate is first polished with 200-mesh sandpaper, then cleaned with anhydrous ethanol, then scrubbed with acetone twice, and dried at 50°C; the above-mentioned coating is evenly applied on the metal surface with a thickness of 120 to 360 μm, and cured at room temperature for 24 hours to obtain a high-adhesion, friction-resistant and anti-corrosion coating.
[0061] The coating performance was tested according to the following national standards. When the coating thickness reached 300μm, the test results were as follows: the Shore hardness measured according to GB / T2411-2008 "Plastics and hard rubber using hardness tester to determine indentation hardness (Shore hardness)" reached 96D, the adhesion measured according to GB / T 5210-2006 "Paint and varnish pull-off method adhesion test" reached 21.5MPa, and the specific wear rate measured according to GB / T23988-2009 "Coating wear resistance determination falling sand method" was 0.8×10 -6 mm 3 / Nm, according to GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes", the neutral salt spray resistance test exceeds 1500 hours.
[0062] Example 2
[0063] A high-adhesion friction-resistant anti-corrosion coating is prepared by the following method:
[0064] 100 g of 4,4'-diaminophenylsulfone and 2 parts of dimethylimidazole were placed in a reactor and heated to 100°C. Then, 200 g of polyethylene glycol bismaleimide resin was added to the reactor at a speed of 1000 rpm, and the mixture was stirred for reaction for 15 minutes. Then, 700 g of 5,5'-di(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin and 400 g of dopamine methacrylamide were added, and the mixture was stirred for reaction for 30 minutes to obtain a uniform mixed system.
[0065] The reactor was removed from the heat source, stirring was continued, the temperature was lowered to room temperature, and then 600 g of acetone, 20 g of zinc powder, an anti-corrosion reinforcing filler, and 50 g of alumina flakes, an anti-friction filler, were added, and ultrasonic stirring was performed for 30 minutes to obtain a highly adhesive anti-friction and anti-corrosion coating material.
[0066] The surface of the metal substrate is first polished with 200-mesh sandpaper, then cleaned with anhydrous ethanol, then scrubbed with acetone twice, and dried at 50°C; the above-mentioned coating is evenly applied on the metal surface with a thickness of 120 to 360 μm, and cured at room temperature for 24 hours to obtain a high-adhesion, friction-resistant and anti-corrosion coating.
[0067] The coating performance was tested according to the national standard shown in Example 1. When the coating thickness reached 300 μm, the test results were as follows: the Shore hardness of the anti-corrosion coating reached 94D, the adhesion reached 24.3 MPa, and the specific wear rate was 0.8×10 -6 mm 3 / Nm, neutral salt spray resistance over 1500 hours.
[0068] Example 3
[0069] The invention discloses a high-adhesion friction-resistant anti-corrosion coating, which is prepared by the following method:
[0070] 80g of 4,4'-diaminophenylsulfone and 70g of dimethylimidazole were placed in a reactor and heated to 80°C. Then, 200g of polyethylene glycol bismaleimide resin was added to the reactor at a speed of 1000 rpm, and the mixture was stirred for reaction for 10 minutes. Then, 650g of 5,5'-di(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin and 200g of dopamine methacrylamide were added, and the reaction was continued by stirring for 30 minutes to obtain a uniform mixed system.
[0071] Remove the reactor from the heat source, keep stirring, lower the temperature to room temperature, then add 1000g acetone, 20g anti-corrosion reinforcing filler zinc powder and 10g anti-corrosion reinforcing filler magnesium powder; 200g friction-resistant filler flaky aluminum oxide, and stir ultrasonically for 30 minutes to obtain a high-adhesion friction-resistant anti-corrosion coating.
[0072] The surface of the metal substrate is first polished with 200-mesh sandpaper, then cleaned with anhydrous ethanol, then scrubbed twice with acetone, and dried at 50°C; the above-mentioned coating is evenly applied to the metal surface with a thickness of 120 to 360 μm, and cured at room temperature for 20 hours to obtain a high-adhesion, friction-resistant and anti-corrosion coating.
[0073] The coating performance was tested according to the national standard shown in Example 1. When the coating thickness reached 300 μm, the test results were as follows: the Shore hardness of the anti-corrosion coating reached 98D, the adhesion reached 22.9 MPa, and the specific wear rate was 0.8×10 -6 mm 3 / Nm, neutral salt spray resistance over 1500 hours.
[0074] Example 4
[0075] The invention discloses a high-adhesion friction-resistant anti-corrosion coating, which is prepared by the following method:
[0076] 30 g of 4,4'-diaminophenylsulfone and 100 g of dimethylimidazole were placed in a reactor and heated to 80°C. Then, 200 g of polyethylene glycol bismaleimide resin was added to the reactor at a speed of 1000 rpm, and the mixture was stirred for reaction for 20 minutes. Then, 600 g of 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin and 150 g of dopamine methacrylamide were added, and the mixture was stirred for reaction for 20 minutes to obtain a uniform mixed system.
[0077] Remove the reactor from the heat source, keep stirring, lower the temperature to room temperature, then add 1500g acetone, 20g anti-corrosion reinforcing filler zinc powder and 10g anti-corrosion reinforcing filler aluminum powder; 100g friction-resistant filler flaky aluminum oxide and 100g friction-resistant filler flaky aluminum nitride, and stir ultrasonically for 30 minutes to obtain a high-adhesion friction-resistant anti-corrosion coating.
[0078] The surface of the metal substrate is first polished with 200-mesh sandpaper, then cleaned with anhydrous ethanol, then scrubbed twice with acetone, and dried at 50°C; the above-mentioned coating is evenly applied to the metal surface with a thickness of 120 to 360 μm, and cured at room temperature for 12 hours to obtain a high-adhesion, friction-resistant and anti-corrosion coating.
[0079] The coating performance was tested according to the national standard shown in Example 1. When the coating thickness reached 300 μm, the test results were as follows: the Shore hardness of the anti-corrosion coating reached 98D, the adhesion reached 21.9 MPa, and the specific wear rate was 0.8×10 -6 mm 3 / Nm, neutral salt spray resistance over 1500 hours.
[0080] Example 5
[0081] The invention discloses a high-adhesion friction-resistant anti-corrosion coating, which is prepared by the following method:
[0082] 30g of 4,4'-diaminophenylsulfone, 40g of diethylenetriamine and 100g of dimethylimidazole were put into a reactor and heated to 70°C. Then, 100g of polyethylene glycol bismaleimide resin was added to the reactor at a speed of 1000 rpm, and the mixture was stirred for reaction for 20 minutes. Then, 600g of 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin and 50g of dopamine methacrylamide were added, and the mixture was stirred for reaction for 20 minutes to obtain a uniform mixed system.
[0083] Remove the reactor from the heat source, keep stirring, lower the temperature to room temperature, then add 800g of acetone, 20g of anti-corrosion reinforcing filler zinc powder and 10g of anti-corrosion reinforcing filler aluminum powder; 100g of friction-resistant filler flaky aluminum oxide and 100g of friction-resistant filler flaky aluminum nitride, and stir ultrasonically for 30 minutes to obtain a high-adhesion friction-resistant and anti-corrosion coating.
[0084] The surface of the metal substrate is first polished with 200-mesh sandpaper, then cleaned with anhydrous ethanol, then scrubbed twice with acetone, and dried at 50°C; the above-mentioned coating is evenly applied to the metal surface with a thickness of 120 to 360 μm, and cured at room temperature for 12 hours to obtain a high-adhesion, friction-resistant and anti-corrosion coating.
[0085] The coating performance was tested according to the national standard shown in Example 1. When the coating thickness reached 300 μm, the test results were as follows: the Shore hardness of the anti-corrosion coating reached 96D, the adhesion reached 23.6 MPa, and the specific wear rate was 0.8×10 -6 mm 3 / Nm, neutral salt spray resistance over 1500 hours.
[0086] Comparative Example 1
[0087] This comparative example is basically the same as Example 2, except that the chemical raw material bisphenol A type epoxy resin is used to replace the 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin, which is the GT6097 type epoxy resin of Huntsman.
[0088] The coating performance was tested according to the national standard described in Example 1. When the coating thickness reached 300 μm, the test results were as follows: the Shore hardness of the anti-corrosion coating reached 80D, the adhesion reached 10.1 MPa, and the specific wear rate was 1.3×10 -6 mm3 / Nm, neutral salt spray resistance for 780 hours.
[0089] Comparative Example 2
[0090] This comparative example is substantially the same as Example 2, except that bismaleimide resin is used to replace polyethylene glycol bismaleimide resin.
[0091] The coating performance was tested according to the national standard described in Example 1. When the coating thickness reached 300 μm, the test results were as follows: the Shore hardness of the anti-corrosion coating reached 94D, the adhesion reached 17.5 MPa, and the specific wear rate was 1.2×10 -6 mm 3 / Nm, neutral salt spray resistance 1100 hours.
[0092] Comparative Example 3
[0093] This comparative example is substantially the same as Example 2, except that methyl methacrylate is used to replace dopamine methacrylamide.
[0094] The coating performance was tested according to the national standard described in Example 1. When the coating thickness reached 300 μm, the test results were as follows: the Shore hardness of the anti-corrosion coating reached 88D, the adhesion reached 13.1 MPa, and the specific wear rate reached 1.0×10 -6 mm 3 / Nm, neutral salt spray resistance 1200 hours.
[0095] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-adhesion, friction-resistant and anti-corrosion coating, characterized in that: The composition comprises the following raw materials in parts by weight: 20-80 parts of epoxy resin, 5-40 parts of composite resin, 5-40 parts of grafting monomer, 0.5-10 parts of anti-corrosion reinforcing filler, 1-20 parts of friction-resistant filler, 5-40 parts of curing agent and 50-150 parts of acetone.
2. A high-adhesion friction-resistant anti-corrosion coating according to claim 1, characterized in that: The epoxy resin is a 5,5'-bis(hydroxymethyl)-[1,1'-biphenyl]-2,2',3,3'-tetrol glycidyl ether type epoxy resin.
3. The high-adhesion friction-resistant anti-corrosion coating according to claim 1, characterized in that: The composite resin is polyethylene glycol bismaleimide resin.
4. The high-adhesion friction-resistant anti-corrosion coating according to claim 1, characterized in that: The grafting monomer is dopamine methacrylamide.
5. A method for preparing a highly adhesive friction-resistant anti-corrosion coating according to any one of claims 1 to 4, characterized in that: The steps include: The curing agent is heated, and the composite resin is added under stirring conditions, and after stirring and reacting, the epoxy resin and the grafting monomer are added, and after stirring and reacting, a mixed system is obtained; The mixed system is cooled, acetone, anti-corrosion reinforcing filler and friction-resistant filler are added, and after stirring, a high-adhesion friction-resistant anti-corrosion coating is obtained.
6. The method for preparing a highly adhesive friction-resistant anti-corrosion coating according to claim 5, characterized in that: The curing agent is heated to 70-120°C.
7. The method for preparing a highly adhesive friction-resistant anti-corrosion coating according to claim 5, characterized in that: After the curing agent is heated, the composite resin is added at a rotation speed of 800 to 1200 rpm, the rotation speed is maintained and stirred for reaction for 5 to 40 minutes, and then the epoxy resin and the grafting monomer are added, and the stirring reaction is continued for 50 to 30 minutes to obtain a mixed system.
8. The method for preparing a highly adhesive friction-resistant anti-corrosion coating according to claim 5, characterized in that: The mixed system is cooled to 15-35° C., acetone, anti-corrosion reinforcing filler and friction-resistant filler are added, and stirred for 5-60 minutes to obtain a highly adhesive friction-resistant anti-corrosion coating.
9. The method for preparing a highly adhesive friction-resistant anti-corrosion coating according to claim 8, characterized in that: After adding acetone, anti-corrosion reinforcing filler and friction-resistant filler, ultrasonic stirring is performed for 5 to 60 minutes.
10. The use of a high-adhesion friction-resistant anti-corrosion coating as claimed in any one of claims 1 to 4, characterized in that: include: The coating is applied to a substrate, which is a metal or an alloy, to form a coating.